COVID-19 associated coagulopathy in septic critically ill patients - a retrospective cohort study - Mirza Kovačević; Nermina Rizvanović; Adisa Šabanović Adilović; Senada Čaušević (Medicinski glasnik, 2023)
Aim: To determine the relationship between coagulation disorders and septic condition in COVID-19 critically ill patients. Methods: Data from 99 patients who presented with COVID-19 acute hypoxemic respiratory failure (CAHRF) were divided into two groups: Group 1- patients who developed sepsis, and Group 2 - patients who developed septic shock. Age, sex, comorbidities, quick Sequential Organ Failure Assessment (qSOFA) score, vasopressor and inotrope requirement, laboratory findings (platelets, neutrophils, lymphocytes, procalcitonin - PCT, C-reactive protein, fibrinogen, D-dimer, sepsis-induced coagulopathy - SIC, and disseminated intravascular coagulation - DIC score) were recorded on the day of admission and on the day of starting invasive mechanical ventilation. The primary outcome was to establish COVID-19 associated coagulopathy with sepsis and septic shock; the secondary outcome measure was incidence of coagulopathy in septic COVID-19 critically ill patients. Results: The most common coagulation abnormality was international normalized ratio (INR) (p=0.019) for Group 2, followed by the values of inflammatory parameters PCT (p=0.002) and lymphocytes (p=0.011) also for Group 2. The statistical significance of SIC score was observed for both groups (p=0.007) and p=0.012, respectively. Norepinephrine (p=0.000) and dobutamine (p=0.000) for Group 2, qSOFA for both groups (p = 0.000) were statistically significant. Conclusion: The observed coagulation abnormalities met the criteria for a SIC diagnosis, therefore, the management of coagulation disorders at this stage of the disease should follow the management of a septic condition.
Keywords: coagulation disorders; incidence; sepsis